Pengaruh Media Video Animasi Fabel terhadap Kemampuan Membaca Pemahaman Cerita Fabel Siswa Kelas II UPTD SDN Keleyan 1 Socah - Ilham Widiyanto Saputra; Dya Qurotul A’yun (Mataram University, 2026)
This research is motivated by the low ability to read fable comprehension stories of second-grade students of UPTD SDN Keleyan 1 Socah. This study aims to determine the effect of using animated fable video media on the ability to read fable comprehension stories of second-grade students of UPTD SDN Keleyan 1 Socah. The study used a quantitative approach with the Quasi Experimental Design method through the Nonequivalent Control Group Design. The study population was all second-grade students consisting of class IIA as the control class of 15 students and class IIB as the experimental class of 16 students. Data collection techniques used tests in the form of pretest and posttest. The research instrument has met the requirements of validity and reliability with a pretest Cronbach's Alpha value of 0.741 and a posttest of 0.743. Data analysis was carried out using normality tests, homogeneity tests, and Independent Samples t-test hypothesis tests with the help of SPSS version 23. The results showed that the average posttest score of the experimental class was 83.75 higher than the control class of 68.00. The results of the hypothesis test obtained a Sig. value. (2-tailed) of 0.000 < 0.05, so H₀ is rejected and Ha is accepted. Thus, there is a significant effect of the use of animated fable video media on the reading comprehension skills of second-grade students at the UPTD SDN Keleyan 1 Socah. Animated fable video media has been proven to improve students' comprehension of reading content through the presentation of interesting, interactive, and easy-to-understand material.